The report. Indonesia 2009 ([London?] Oxford Business Group, 2009)
Provides a country profile of Indonesia, including politics, the economy, banking, capital markets, insurance, transport, energy, construction and real estate, telecoms and IT, industry, plantations and agriculture, mining, and tourism.
Mode of access: World Wide Web.
System requirements: Adobe Acrobat to view PDF document.
Keywords: Indonesia -- Economic conditions -- 1997-; Indonesia -- Economic policy